FORMING DISTANCE TESTING AS AN INNOVATIVE TECHNOLOGY OF DISTANCE EDUCATION - Andros, Myroslav Yevheniiovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The Concept of the New Ukrainian School declares changes in approaches to assessment of learning outcomes. One such approach is formative assessment, which is considered to be an assessment to improve learning. Formative assessment creates an opportunity for the teacher to monitor the process of progress of the student to the educational goals and make timely adjustments to the educational process. For the learner, formative assessment serves as a recommendation for action, not a pedagogical final verdict, especially in modern conditions of using distance (blended) learning technologies in extremely complex educational conditions.